Assessment of Rationality in Prescribing Practice of Antibiotics in Out Patient Department at Moradabad - Sharma, Aditya; Prasad, Neelkant; Porwal, Mayur; Shrivastav, Alankar; Shrivastav, Alankar; Khan, Najam Ali (Indian Journal of Pharmacy Practice)
Objective: Rational use of drugs requires that patients receive medications appropriate to their clinical need. Prescription errors are the most common leading problems for patients and additional costs of the health system. Methodology: A prospective study was carried out after collecting 243 prescriptions of outpatients in the Moradabad city for a period of 3 months for evaluating the prescribing errors. Prescription’s copies were obtained from the various community pharmacies of Moradabad. Result: The collected data was screened that such errors were almost in a similar proportion of the male patients as well as female patients (54.08% and 51% respectively). Unauthorized synergistic combinations of antibiotics with drug-drug interactions were greater in male patients (20%) than in female patients (7.69%). Maximum error was found in advising and patient counselling i.e.77.14% in male and 80.77% in female. Conclusion: Information on prescriptions and their incomplete or poor diagnosis may contribute to prescribing errors. Prescription errors need to be acknowledged, taken seriously, discussed openly and actions taken in a blame free culture.
Keywords: Prescription; Antibiotics; Outpatient department (OPD); Error